Hallyu (Korean Wave) as Part of South Korea’s Cultural Diplomacy and Its Impact on Cultural Hybridity in Indonesia - Teguh Puja Pramadya; Jusmalia Oktaviani (Universitas Jenderal Ahmad Yani, 2016)
Korean Wave or ‘hallyu’ is a phenomenon of the spread of South Korean culture, which is very interesting to learn. Some influences in the entertainment industry this year, especially in Indonesia is pronounced, with many types of Korean cultural products that can be found in various forms, such as music, movies, culinary, fashion, language courses, and so on. As part of the strategy of cultural diplomacy, by the South Korean government, 'hallyu' is used optimally by the government, to promote South Korean culture. However, the spread of 'hallyu' now is not only an indicator of the success of cultural diplomacy on the part of South Korea’s government alone. The cultural hybridity also helps' hallyu' widespread, where the international community would accept the foreign culture, like Korean culture as part of their lifestyle.